Modeling of COVID-19 Pandemic vis-à-vis Some Socio-Economic Factors - Oshinubi, Kayode; Rachdi, Mustapha; Demongeot, Jacques (Frontiers in Applied Mathematics and Statistics, 2022)
The impacts of COVID-19 outbreak on socio-economic status of countries across the globe cannot be over- emphasized as we examine the role it played in various countries. A lot of people were out of jobs, many households were careful of their spending and a greater social fracture of the population in fourteen different countries has emerged. We considered periods of infection spread during the first and second wave in Organization for Economic Co-operation and Development (OECD) countries and countries in Africa, that is developed and developing countries alongside their social-economic data. We established a mathematical and statistical relationship between Theil and Gini index, then we studied the relationship between the data from epidemiology and socio-economic determinants using several machine learning and deep learning methods. High correlations was observed between some of the socio-economic and epidemiologic parameters and we predicted three of the socio-economic variables in order to validate our results. These result shows a sharp difference between the first and second wave of the pandemic confirming the real dynamics of the spread of the outbreak in several countries and ways by which it was mitigated.